Argon gas plasma to decontaminate and extend shelf life of milk. Issue 11 (20th June 2017) - Ponraj, Sri B.; Sharp, Julie A.; Kanwar, Jagat R.; Sinclair, Andrew J.; Kviz, Ladge; Nicholas, Kevin R.; Dai, Xiujuan J.
Abstract : Treatment of milk with argon gas plasma was investigated for its ability to kill bacteria and increase shelf life and compared with commercially pasteurized milk. The discharge was generated by a nanosecond pulse generator using the needle point‐to‐plate electrode. The total bacterial count of 6.8 log CFU/mL in raw milk was reduced to 1.9 log CFU/mL after 2 min of plasma treatment and 2.2 log CFU/mL after 30 min of pasteurization. The plasma treated milk stored at 4 °C showed no significant changes in the bacterial count for 6 weeks while the bacterial counts in pasteurized milk were significantly increased from 2.2 to 4.2 log CFU/mL after 2 weeks. These results demonstrated plasma treatment as an alternative way to decontaminate and increase shelf life of milk. Abstract : This paper demonstrates the use of argon gas plasma to reduce the bacterial count and prolong the shelf life in bovine milk.